Labour markets and wages in Australia 2010 - Jefferson, Therese; Preston, Alison (Sage Publications Ltd., 2011)
In this article we present data on earnings and hours in 2010 and, using data over a longer time frame, show how the character of the Australian labour market has significantly changed in recent decades. Among other things, we demonstrate a continued shift towards part-time work and, across full-time and part-time labour markets, a change in the distribution of jobs towards more highly skilled occupations. We continue to argue that traditional indicators of labour-market activity, such as headline unemployment and earnings in full-time employment, are only able to partially explain the health of the labour market. There is an urgent need to better understand other dimensions such as underemployment, part-time employment and part-time earnings.